2016
DOI: 10.1002/nau.23116
|View full text |Cite
|
Sign up to set email alerts
|

Mobile app for treatment of stress urinary incontinence: A randomized controlled trial

Abstract: The mobile app treatment was effective for women with SUI and yielded clinically relevant improvements. This app may increase access to first-line treatment and adherence to PFMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
318
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 140 publications
(332 citation statements)
references
References 21 publications
9
318
3
2
Order By: Relevance
“…These studies differ from ours in terms of treatment comparison (either a group receiving postal information or a group receiving postponed treatment, rather than comparison to usual care). 5,6 The main strength of this study will be in the combination of research methods used. A mixed-methods study design is frequently used in social science and can make an important contribution to RCTs evaluating health service interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies differ from ours in terms of treatment comparison (either a group receiving postal information or a group receiving postponed treatment, rather than comparison to usual care). 5,6 The main strength of this study will be in the combination of research methods used. A mixed-methods study design is frequently used in social science and can make an important contribution to RCTs evaluating health service interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of an app-based treatment for stress UI was assessed in Swedish women in a community setting, and not only produced clinically relevant symptom improvement but also reduced pad usage compared with postponed treatment. 5 In other research, an internet-based training program was shown to be a cost-effective alternative for treating stress UI when compared with a treatment program sent by post. 6 However, studies evaluating app-based treatment for all three types of UI (ie, stress, urgency, and mixed UI) are lacking, and app-based treatment for UI has never been compared to care as usual.…”
mentioning
confidence: 96%
“…The trial was registered at clinicaltrials.gov (ID: NCT01848938), and the trial results were described in detail elsewhere [14]. …”
Section: Methodsmentioning
confidence: 99%
“…Samuelsson et al presented a smartphone application as an easily accessible, cost effective treatment for stress urinary incontinence (SUI) and they were awarded joint winner of the Conservative Management Award. Given that many are still smartphone illiterate and 40% perform pelvic floor exercises incorrectly this application can provide an adjunct to, rather than replace, individualized pelvic floor training with digital palpation (Abstracts 16, 521, 526).…”
Section: Introductionmentioning
confidence: 99%